Meta-Analysis of Extracellular Vesicle microRNAs in Host Immune Response to Bacterial Infection - Al-Sadawi, Aqeel A.; Ali Reyadh Medhat; Ruaa Kareem Surhan; Ahmed Al Obaidi (Universitas Muhammadiyah Sidoarjo, 2025)
Extracellular vesicle-associated microRNAs (EV-miRNAs) have gained recognition as key regulators of immune processes during bacterial infections. This meta-analysis aims to comprehensively assess the expression dynamics, diagnostic value, and immunological implications of EV-associated miRNAs during bacterial infections. A systematic review of studies indexed in PubMed, Scopus, and Web of Science was performed through May 2025, following PRISMA 2020 criteria. A total of 42 studies involving 2,348 samples from human and animal sources were included. Data extracted covered miRNA profiles, detection techniques (RT-qPCR, RNA-seq, microarray), infection types, and sample origins (plasma, serum, BAL, CSF). A random-effects meta-analysis was conducted, supplemented by subgroup and sensitivity analyses. Publication bias was evaluated using funnel plots and Egger’s test. Five EV-miRNAs—miR-155, miR-146a, miR-21, miR-223, and miR-29a—were found to be significantly upregulated in ≥10 studies. The most prominent pooled effect size was observed for miR-21 (SMD: 1.52; 95% CI: 1.10–1.94; p < 0.0001). Subgroup analyses revealed stronger expression in Gram-negative infections and in plasma-based samples. RNA-seq outperformed RT-qPCR in sensitivity. No significant publication bias was detected. Sensitivity tests confirmed the robustness of the findings. Functional enrichment pointed to roles in NF-κB/TLR signaling, macrophage polarization, and cytokine modulation. EV-associated miRNAs show consistent and significant dysregulation during bacterial infections, highlighting their potential as biomarkers and immunoregulatory agents. These findings warrant further validation in prospective and functional studies. Highlights: Five EV-miRNAs (miR-155, miR-146a, miR-21, miR-223, and miR-29a) were consistently upregulated during bacterial infections. Expression changes were more pronounced in Gram-negative infections and plasma-based samples, with RNA-seq showing the highest sensitivity. These EV-miRNAs are strongly linked to NF-κB/TLR signaling, macrophage polarization, and cytokine modulation, highlighting their biomarker and therapeutic potential.